Teachers' and Students' Perceptions of The Implementation Of Diagnostic Assessment In Indonesian Language Learning In Grade III Elementary School - Rael Ariel Situmorang; Osco Parmonangan Sijabat; Sukardo Sitohang (CV Putra Publisher, 2026)
The way teachers and students perceive diagnostic assessment plays a decisive role in how effectively it is implemented in real classrooms. This study was designed to quantitatively capture how Grade III teachers and students at UPTD SD Negeri 122384 Pematangsiantar make sense of the diagnostic assessment practices they experience in Indonesian Language learning, while also examining whether their perspectives align.A quantitative descriptive survey design was employed. Respondents consisted of 2 Grade III Indonesian Language teachers (total sampling) and 20 Grade III students (purposive sampling). Data were collected using Likert-scale questionnaires tested for validity (r >= 0.444) and reliability (Cronbach alpha: teachers = 0.921; students = 0.941). Analysis relied on descriptive statistics based on Ideal Mean (Mi) and Ideal Standard Deviation (SDi).The results are encouraging: teachers' perceptions fall in the very positive category with a converted score of 80.47/100, while students' perceptions stand at 81.50/100. Of the 20 students, 60% are in the very positive category and the remaining 40% in the positive category. The gap between both groups is only 1.03 points on a 0-to-100 scale, reflecting genuine alignment. One notable finding: the teachers' conative dimension (consistency in assessment follow-up) scores lower than the other two dimensions, signaling the need to strengthen implementation. These findings support the provision of standardized assessment instrument templates and peer coaching programs at the elementary school level